Cost-Effectiveness of the FDA Added Sugar Labeling to Reduce Cancer Burden in the United States (OR28-03-19). (13th June 2019) - Du, Mengxi; Griecci, Christina; Cudhea, Frederick; Kim, David; Eom, Heesun; Wilde, Parke; Wong, John; Ruan, Mengyuan; Rehm, Colin; Michaud, Dominique; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract: Objectives: Meta-analyses have identified obesity as an independent risk factor for 13 cancers and added sugars as a contributor to obesity. In 2016, the new Nutrition Facts label on US packaged foods mandated the inclusion of added sugar content. We assessed the health outcomes, costs, and cost-effectiveness of this policy on obesity-related cancer burdens among 250 million US adults over their lifetime. Methods: We populated the Diet Cancer Outcome Model (DiCOM), a probabilistic cohort-state transitional model, to evaluate two effects of the policy on (a) consumer behavior alone; and (b) consumer behavior plus industry reformulation. Policy effect on consumer behavior was derived from a meta-analysis of calorie labeling; and on industry reformulation, from the FDA's regulatory impact analysis and the UK sugar reformulation strategy. Effects of added sugar on obesity and obesity on cancer incidence were derived from meta-analyses and published literature. Cost-effectiveness was evaluated as net costs with 3% annual discounting, under both government affordability and societal perspectives. Results: We estimated that, based on consumer responses alone, the added sugar labeling would prevent 35, 500 new cancer cases (95% uncertainty interval [UI]: 12, 300 to 65, 800) and 16, 700 cancer deaths (95% UI: 5720 to 31, 400) and gain 113, 000 quality-adjusted life years (QALYs) (95% UI: 38, 800 to 210, 000) over a lifetime. Adding potential additional effects on industry reformulation, corresponding values were 79, 700 new cancer cases (95% UI: 28, 100 to 140, 000), 37, 500 cancer deaths (95% UI: 13, 200 to 66, 000), and 253, 000 QALYs (95% UI: 89, 600 to 444, 000). Policy would result in estimated net cost savings of 8600 M (95% UI: 6900 M to 11, 000 M) from governmental affordability and 7500 M (5400 M to 9900 M) from societal perspectives based on consumer responses alone. With industry reformulation, net savings were 19, 000 (95% UI: 15, 000 M to 23, 000 M) and 16, 000 M (95% UI: 12, 000 M to 20, 000 M), respectively. Conclusions: Our modeling estimates that implementation of the FDA added sugar labeling will lead to significant numbers of averted cancer cases and deaths, with net cost-savings; and that potential industry responses may contribute to similar or larger benefits than consumer responses alone. Funding Sources: NIH/NIMHD. Supporting Tables, Images and/or Graphs: